An anatomy of a priory church : the archaeology, history and conservation of St Mary's Priory Church, Abergavenny - Nash, George (Archaeopress Publishing Ltd, 2015)
Based on documentary evidence, the Priory Church of St Mary's in Abergavenny has been a place of worship since the late 11th century; archaeological evidence though suggests that the site has a much earlier period of use. Over the past 1000 years the church has been radically altered to reflect its wealth, status and sometimes, its decline. During the 18th, 19th and 20th centuries a number of alterations were made that included the complete demolition and rebuild of the nave. This change, along with the Reformation of 1536 and the vandalism of the mid- to late 17th century did not deter the people of Abergavenny from using this most beautiful of spaces. In the recent past, the late Jeremy Winston did much to add his signature onto the priory's fabric making St Mary's a most splendid place of worship. This book traces the archaeology, history and conservation of this most impressive building.